Importance-Performance Analysis for Improving Online Learning in Business and Management Programme - Abdul Shukor, Syadiyah (International Business Education Journal, 2023)
Online learning has become the new standard in higher education since the COVID-19 epidemic. In order to be effective, colleges and universities must evaluate the delivery of online classes using relevant data gathered from their students. This paper demonstrates the use of importance-performance analysis to continuously improve online learning quality. Undergraduate students, who are enrolled in Business and Management programme at a higher learning institution located in Negeri Sembilan, Malaysia are invited to participate in this survey via online survey questionnaire. A total of 239 responses are received and analysed using importance-performance analysis technique. The results show that facilitating conditions, namely technology and interaction fell into the ‘Concentrate Here’ quadrant; course delivery and instructor factors in the ‘Keep Up the Good Work’ quadrant; and learners’ readiness in the ‘Low Priority’ quadrant. From the result, it is suggested that technology and interaction attributes should be paid special attention. Thus, importance-performance analysis can significantly contribute to the continued improvement of online learning delivery quality.